Multi-level governance and adaptive capacity in West Africa - Brockhaus, Maria; Djoudi, H.; Kambire, H. (Ubiquity Press, Ltd., 2012)
In most regions in West Africa, livelihoods depend heavily on forest ecosystem goods and services, often in interplay with agricultural and livestock production systems. Numerous drivers of change are creating a range of fundamental economic, ecological, social and political challenges for the governance of forest commons. Climate change and its impacts on countries’ and regions’ development add a new dimension to an already challenging situation. Governance systems are challenged to set a frame for formulating, financing and implementing adaptation strategies at multiple layers, often in a context of ongoing institutional changes such as decentralisation. A deeper understanding of actors, institutions and networks is needed to overcome barriers in socio-ecological systems to adaptation and enable or enhance adaptive capacity. In this paper, we explore the relationship between governance and adaptive capacity, and characterise and assess the effects of a set of variables and indicators related to two core variables: Institutional flexibility, and individual and organisational understandings and perceptions. We present a comparative analysis with multiple methods based on a number of case studies undertaken at different levels in Burkina Faso and Mali. One of the key findings indicates the importance and influence of discourses and narratives, and how they affect adaptive capacity at different levels. Revealing the ideological character of discourses can help to enable adaptive capacity, as it would break the influence of the actors that employ these narratives to pursuit their own interests.